Peningkatan Literasi Keagamaan dan Digital bagi Siswa Madrasah Melalui Kelas Kreatif Berbasis Teknologi - Wali, Wali Ja'far Shudiq; Zainal Arifin; Rio Ahmad Syaikhu; Abd Wafi; Moh.Januar Rizqi Minallah (Yayasan Literasi Altruis Khatulistiwa, 2025)
Amidst the rapid pace of globalization and technological development, madrasah students are required to be able to integrate spiritual values with digital skills in order to adapt, innovate, and remain committed to religious principles. Through technology-based creative classes, this program serves as a strategic means to build a transformative learning ecosystem that not only strengthens religious literacy but also fosters creativity, collaboration, and digital literacy as tools to face challenges. The participatory learning method was implemented through a series of training and mentoring sessions that combined religious material with digital skills, such as creating educational content, utilizing social media positively, and using interactive learning applications. The target of this activity was students of Madrasah Ibtidaiyah Darul Ihsan who had an interest in technology and religion. The results of the activity showed an increase in students' understanding of Islamic values to 85% and basic skills to 82% in using technology creatively and responsibly. This activity proves that the integration of religious values and digital skills enhances the ability to create a learning process that is relevant, interesting, and has a positive impact on the younger generation of madrasah students